Surface analysis of (Ti,Mg)N coated bone fixation devices following the rabbit femur surgery - Sabouni, Kenda; Ozturk, Yetkin; Kacar, Erkan; Kose, Gamze Torun; Kok, Fatma Nese; Kazmanli, Muhammet Kursat; Urgen, Mustafa Kamil; Onder, Sakip (IOS PRESS, 2023)
BACKGROUND: Magnesium (Mg) enhances the bone regeneration, mineralization and attachment at the tissue/biomaterial interface. OBJECTIVE: In this study, the effect of Mg on mineralization/osseointegration was determined using (Ti,Mg)N thin film coated Ti6Al4V based plates and screws in vivo. METHODS: TiN and (Ti,Mg)N coated Ti6Al4V plates and screws were prepared using arc-PVD technique and used to fix rabbit femur fractures for 6 weeks. Then, mineralization/osseointegration was assessed by surface analysis including cell attachment, mineralization, and hydroxyapatite deposition on concave and convex sides of the plates along with the attachment between the screw and the bone. RESULTS: According to Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analyses; cell attachment and mineralization were higher on the concave sides of the plates from both groups in comparison to the convex sides. However, mineralization was significantly higher on Mg-containing ones. The mean gray value indicating mineralized area after von Kossa staining was found as 0.48 +/- 0.01 and 0.41 +/- 0.04 on Mg containing and free ones respectively. Similarly, Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD) analyses showed that hydroxyapatite growth was abundant on the Mg-containing and concave sides of the plates. Enhanced mineralization and strong attachment to bone were also detected in EDS and SEM analyses of Mg-containing screws. CONCLUSION: These findings indicated that (Ti,Mg)N coatings can be used to increase attachment at the implant tissue interface due to accelerated mineralization, cell attachment, and hydroxyapatite growth.
Keywords: Magnesium; mineralization; osseointegration; bone; HYDROXYAPATITE FORMATION; BIODEGRADABLE MAGNESIUM; ORTHOPEDIC BIOMATERIALS; CELL-DIFFERENTIATION; IN-VITRO; COATINGS; ALLOYS; CORROSION; BEHAVIOR; OSTEOINTEGRATION; Engineering; Materials Science